Perancangan Tampilan Landing Page Lasem Eksotis Sebagai Media Digital Advertising Dalam Upaya Perluasan Jangkauan Pasar Produk Umkm - Muhammad Zaki Raushan Fikri; Noor Hasyim (Universitas Dian Nuswantoro, 2026)
Changes in consumer behavior in the digital era require Micro, Small, and Medium Enterprises (MSMEs) not only to rely on product quality, but also to strengthen brand image through structured, consistent, and persuasive digital media. Rumah BUMN Rembang has assisted hundreds of MSMEs and initiated the collective campaign Lasem Eksotis to promote culture-based local products, particularly Lasem batik and leather crafts. However, the digital promotion of assisted MSMEs remains fragmented across multiple platforms, resulting in weak visual consistency and underdeveloped cultural storytelling, which limits audience awareness, interest, and trust. This study aims to design a digital advertising interface in the form of a landing page themed Lasem Eksotis as an integrated promotional medium and a visual storytelling tool to support the expansion of MSMEs' market reach. The study employs a qualitative descriptive approach using a User-Centered Design (UCD) paradigm, positioning MSME actors and Rumah BUMN facilitators as primary users. Data were collected through triangulation methods, including field and digital observation, semi-structured interviews, literature review, and visual documentation. Data analysis was conducted qualitatively through data reduction, thematic categorization, and 5W+1H analysis to map user needs. The result is a landing page design concept functioning as a digital campaign hub that integrates cultural narratives, MSME profiles, product showcases, artisan stories, credibility elements, and soft-conversion calls to action with a mobile-first and sustainable user experience.